Enhancing entrepreneurship learning: An evaluation of graduate profile-aligned courses at FEBI UIN Antasari - Sahal, Lutpi; Qamaruddin, Muhammad (Journal of Islamic Economics Lariba, 2024)
IntroductionIn the dynamic landscape of higher education in Indonesia, the Faculty of Islamic Economics and Business (FEBI) at the State Islamic University (UIN) Antasari Banjarmasin faces the challenge of improving the quality of education, particularly in courses designed to align with the entrepreneurship graduate profiles. Entrepreneurial education is emerging as a solution to the high unemployment rates among college graduates.ObjectivesThis study aimed to evaluate courses aligned with entrepreneurship graduate profiles at FEBI UIN Antasari, focusing on enhancing students' entrepreneurial motivation. This research employs the Context, Input, Process, Product (CIPP) evaluation model to examine various learning components.MethodThe study used a combination of quantitative and qualitative research methods, including surveys, focus group discussions (FGDs), and in-depth interviews with students, faculty managers, and lecturers. The evaluation focused on curriculum development, teaching materials, collaboration with practitioners, practicum facilities, lecturer training and certification, student internships, talent mapping, and alumni networks.ResultsThe findings highlight the importance of curriculum reviews involving entrepreneurship practitioners, development of standardized teaching materials, practical entrepreneurship activities, and collaboration between academics and practitioners. Student feedback indicates a positive evaluation of the courses, but also identifies areas for improvement, such as updating teaching materials, enhancing teaching methods, and maximizing the use of infrastructure.ImplicationsThe results underscore the need for continuous improvement in entrepreneurial education to foster entrepreneurial motivation and produce graduates equipped to thrive in a competitive job market. Enhancing practical experiences, fostering collaboration, and updating teaching methods are crucial steps for improving the quality of entrepreneurship education.Originality/NoveltyThis study provides a comprehensive evaluation of entrepreneurship courses aligned with graduate profiles, offering valuable insights into the effectiveness of current educational practices and recommendations for future improvement.